Risk of Factor on History Disease with Nutritional Status on Toddlers Aged 24-59 Months in Pidie Jaya District - Zuhra Tun Nur; Suryana Suryana (Universitas Teuku Umar, 2021)
ABSTRACTThe nutritional problem has happened in Indonesia. One of them is toddler malnutrition. Children who are malnourished have a low immune system. Thus it is susceptible to infectious diseases. Factors that can prevent nutritional problems in toddlers include the age of weaning and the toddler's immune system. Breastfeeding until the two-years-old, weaning, and body resistance will also affect the toddler's nutritional status. The research aimed to identify the risk factors of disease history on toddler stunting's nutritional status in Pidie Jaya District. The research's implementation was descriptive-analytic with a cross-sectional research design with a sample size of 34 people—data on weaning patterns and disease history obtained through interviews with questionnaires. Anthropometry measurements obtained the nutritional status data of toddlers. Analysis used chi-square test. Based on the results, most of the 14.7% of toddlers had a history of fever, 52.95% of unwilling toddlers. Toddlers with well nutritional status with weight-for-age index 64.7%, skinny nutritional status with weight-for-height index 55.9%, short nutritional status with height-for-age 52.9%, and regular dietary status with BMI-for age index 73.5%. Conclusion there was an influence of children's history disease in the last three months on nutritional status in the index height-for-age P-value = <0.015 (<0.05) with OR 6.0, but there was no influence of sick history on nutritional status with index weight-for-age, weight-for-age and BMI-for-age (P-value >0.05). It was important for the mother to implement a healthy lifestyle, environmental hygiene, and hygiene of the food history to become better.